2023
DOI: 10.1021/acs.jpclett.3c02675
|View full text |Cite
|
Sign up to set email alerts
|

Designing Surface-Defect Engineering to Enhance the Solar-Driven Conversion of CO2 to C2 Products over Zn3In2S6/ZnS

Shuaishuai Liu,
Fang Fan,
Pengxin Li
et al.

Abstract: The manipulation of electronic structure and prevention of photogenerated carriers from being quenched in bulk defects during the photocatalytic CO2 reduction reaction (CRR) have been effectively demonstrated through surface vacancy and defect engineering. In this work, the electronic structure on the surface of Zn3In2S6/ZnS (ZIS/ZnS) is significantly modified by the introduction and control of the surface S vacancies (SV) through Ar-plasma treatment. EPR and XPS analyses confirmed that SV was exclusively pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The peak separation of the peaks at 1022.5 eV and 1045.9 eV in Zn 2p spectrum ( Fig. 2 A) and which was originated from the Zn 2p 3/2 and Zn 2p 1/2 of ZnS [ [27] , [28] ]. In other hand, the S 2p could be deconvoluted into the peaks at 162.5 eV and 163.2 eV, assigned to S 2p 3/2 and S 2p 1/2 of ZnS ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The peak separation of the peaks at 1022.5 eV and 1045.9 eV in Zn 2p spectrum ( Fig. 2 A) and which was originated from the Zn 2p 3/2 and Zn 2p 1/2 of ZnS [ [27] , [28] ]. In other hand, the S 2p could be deconvoluted into the peaks at 162.5 eV and 163.2 eV, assigned to S 2p 3/2 and S 2p 1/2 of ZnS ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…27 28 Generally speaking, the formation energy of an anion is lower than that of a cation. 29 Also, Zn 3 In 2 S 6 with abundant S vacancies has also been employed as a building block to construct heterojunction material to induce directional migration of photoexcited carriers. 22,30 Simultaneously, surface-exposed Zn acid centers of Zn 3 In 2 S 6 exhibit strong Lewis acid properties, which are expected to activate and polarize epoxides for the CO 2 cycloaddition process.…”
Section: Introductionmentioning
confidence: 99%
“…Xia et al found that Zn vacancies in ZnIn 2 S 4 nanosheets optimized CO 2 activation intermediate adsorption energy and thus achieved remarkable faradaic efficiency for CO 2 electroreduction to formate . Generally speaking, the formation energy of an anion is lower than that of a cation . Also, Zn 3 In 2 S 6 with abundant S vacancies has also been employed as a building block to construct heterojunction material to induce directional migration of photoexcited carriers. , …”
Section: Introductionmentioning
confidence: 99%